Association between HbA1c and dyslipidemia among sample of Iraqi Patients with Type2 DM - Hami, Ali M. (Journal of the Faculty of Medicine Baghdad, 2021)
Background: Diabetic Mellitus is considered as a public health concern. More than 8 percent of the United States has diabetes. Diabetes is a serious risk factor for Atherosclerotic cardiovascular disease (ASCVD) and an important cause of mortality. ASCVD is the commonest cause of death in the Western world. Diabetes was defined as a high risk condition for ASCVD. In adults with diabetes with ASCVD or multiple ASCVD risk factors it is important to prescribe high intensity statin to reduce LDL at least to 50%.Objective: To investigate association between dyslipidemia and HbA1c and to detect benefit of using some statins in decreases the risk of CVD.Material and method: A prospective randomized single dose study was carried out at a private clinic in Wasit governorate-Iraq; included patients with type 2 diabetes. Clinical biochemical lab assessment and re assessment was carried out before and after 3 months of receiving Rosuvastatin 20 mg/ day. A questionnaire paper was used, including sociodemographic and clinical features (age, gender, measuring weight, height, and waist circumference; biochemical markers [total cholesterol, HDL, LDL, TG and HbA1c]).Results: A total of 256 type 2 DM patients were included; receiving 20 mg of rosuvastatin as a single dose for 3 consecutive months. 83 (32.4%) of them were males and 173 (67.6%) were females. Mean age of male (52.0710.486) and that of female (53.1110.410). the mean difference of (BMI, WC, HbA1c, LDL, TG, and cholesterol) among all studied sample after treatment was significantly lower than mean difference that measured before treatment, except that for HDL; where it was significantly higher after treatment, P